Antifouling Surface‐Attached Hydrogel Nanocoatings Redefined: Green Solvent‐Based, Degradable, and High‐Performance Protection Against Foulants - Jenny Englert; Marc Palà; Jonas Quandt; Hannah Sieben; Oliver Grottke; Bernd Marx; Gerard Lligadas; Cesar Rodriguez‐Emmenegger (Advanced Materials Interfaces, 2025)
Abstract Antifouling coatings are vital to enhance the performance of medical devices, aiming to mitigate bodily reactions by shielding their surface. Despite significant advancements in antifouling coatings, like those based on zwitterionic monomers and hydroxyl‐functionalized (meth)acrylamides, limitations like decreased antifouling properties after functionalization and complement system activation hinder their application in blood. Here, a novel class of ultrathin surface‐attached hydrogels is presented, consisting of hydrophilic non‐charged green solvent‐based monomers and preventing protein adsorption while offering on‐demand degradability. Unlike the best antifouling brushes, the coatings are easily applicable, unaffected by charges, and free of complement system‐activating groups. The hydrogels are formed using copolymers of N,N‐dimethyl lactamide acrylate (DMLA) and benzophenone acrylate (BPA). Moreover, 5,6‐benzo‐2‐methylene‐1,3‐dioxepane (BMDO) is incorporated to introduce hydrolyzable ester. The coating of state‐of‐the‐art devices is demonstrated with X‐ray photoelectron spectroscopy (XPS), analyze surface energy components, and confirm their antifouling properties with surface plasmon resonance (SPR). The coatings are non‐cytotoxic toward MRC‐5 fibroblasts, exhibit repellency against methicillin‐resistant Staphylococcus aureus (MRSA), and effectively prevent thrombus formation on devices in blood. This work establishes a versatile platform for next‐generation coatings in medical and industrial applications, matching the antifouling efficiency of the most advanced solutions and offering regeneration of substrates by erasing the coating.